Two-dimensional Ca4N2 as a one-dimensional electride [Ca4N2]2+·2e− with ultrahigh conductance. Issue 9 (25th February 2020) - Liu, Xiaofeng; Ding, Zijing; Liu, Jie; Hu, Wei; Yang, Jinlong
Abstract : Two dimensional Ca4 N2 can serve as a one-dimensional electride [Ca4 N2 ] 2+ ·2e − with anionic electrons confined in the surface channels and possess high electrical conductance. Abstract : Electrides possess high electrical conductance and reactivity and are promising for novel applications in electronics and catalysis. Here, we predict a new thermodynamically and kinetically stable two-dimensional (2D) Ca4 N2 using first-principles density functional theory (DFT) calculations. 2D Ca4 N2 can serve as a one-dimensional (1D) electride [Ca4 N2 ] 2+ ·2e − with anionic electrons confined in the surface channels. In particular, we demonstrate that 2D Ca4 N2 possesses high Fermi velocity (0.42 × 10 6 m s −1 ), electron effective Fermi mass (∼1 m e ), ultrahigh charge density (1.14 × 10 15 cm −2 ), and high carrier mobility (215 and 5.29 × 10 6 cm 2 V −1 s −1 at a room temperature of 300 K and a low temperature of 2 K), resulting in ultrahigh conductance up to 0.039 and 966 S respectively for 300 and 2 K, compared to existing 2D materials and the best conductors (Cu and Ag). Furthermore, the first finding of 1D anionic electron behaviour on the surface of 2D materials can be used to stimulate the design of new kinds of electrides for exploring the physics of 1D and quasi-1D systems.